Creative Thinking Enhancement through Environmental Issue Based STEM Learning in Elementary Schools - Jajang Bayu Kelana; Ari Widodo; Irma Rahma Suwarma (Universitas Pendidikan Ganesha, 2025)
Global changes in the 21st century require the strengthening of creative thinking skills at the primary school level to address increasing complexity while fostering environmental awareness. This study aims to analyze and examine the effectiveness of Environmental Issue Based STEM learning in enhancing students’ creative thinking skills. The research employed a quantitative approach with a one group pretest posttest design. The participants were 152 primary school students. Data were collected using a validated creative thinking skills test and supported by interviews to enrich the interpretation of the findings. Data were analyzed using comparative statistical tests to identify differences between pre-intervention and post intervention scores. The results revealed a significant improvement in students’ creative thinking skills after the intervention, although the magnitude of the gain was relatively low. The improvement was more evident in fluency and flexibility, while originality and elaboration developed to a lesser extent. These findings indicate that Environmental Issue-Based STEM learning is effective in stimulating early stage divergent thinking; however, longer interventions and systematic scaffolding are required to optimize all dimensions of creativity. The implication is that instructional design should be structured and sustained to promote deeper and more comprehensive development of students’ creativity.